Survey protocol and the influence of land use on bird communities in southern Ontario coastal marshes - Smith, Lyndsay Ann (My University, 2009)
Concern over recent declines in many wetland-dependent bird species has led to a need to monitor marsh bird populations in response to anthropogenic activities. I conducted point counts and vegetation surveys at 26 coastal wetlands in the Laurentian Great Lakes Region of Canada from 2006-2008 to determine 1) effective methods to monitor marsh birds, and 2) the impacts of land use surrounding coastal wetlands on marsh bird communities. The first part of this dissertation showed that call-broadcasts are effective tools for monitoring marsh birds and that point counts for marsh birds should be conducted from both the shoreline and from the interior of large marshes. Because of the species-area relationship for wetland birds in southern Ontario, sampling effort should increase proportionally with wetland area to attempt the detection of all species present. In the second part of this thesis, I showed that marsh obligate-nesters preferred wetlands in rural areas as opposed to urban areas, while generalist marsh-nesting species showed no apparent difference in use. The Index of Marsh Bird Community Integrity (IMBCI), a biological index used to indicate wetland health, was significantly higher in rural than in urban marshes. Marsh isolation was also an important factor in predicting the marsh bird community, with more isolated wetlands containing fewer obligate species and associated with a lower IMBCI value. Wetlands of Georgian Bay were found to have quite different bird and plant communities than wetlands of Lake Ontario. Even though wetlands of Lake Ontario were considerably more degraded than those in Georgian Bay (according to land use alteration and degree of water quality impairment), these two regions produced similar IMBCI scores, and this draws into question the applicability of some indicators on a basin-wide scale. The results of this thesis indicate how survey protocols in existing wetland bird monitoring programs should be modified and support current literature that urbanization negatively affects the marsh bird community.
Wetland Birds of Southern Ontario
Keywords: biology; study protocol; land use; bird community; southern Ontario; coastal, marsh; Lake Ontario, wetland; Georgian Bay